Utilization of Pharmacist Responders as a Component of a Multidisciplinary Sepsis Bundle. (September 2014) - Flynn, Jeremy D.; McConeghy, Kevin W.; Flannery, Alexander H.; Nestor, Melissa; Branson, Pam; Hatton, Kevin W.
Background: Sepsis and septic shock remain a significant burden on the US health care system. A multidisciplinary response system (Coordinated Response to Sepsis, CaRTS) that included a pharmacist responder was implemented for patients with newly suspected sepsis.Objective: To evaluate the time to appropriate antibiotic administration among patients with the CaRTS intervention compared with historical controls.Method: The CaRTS intervention included an electronic order set as well as activation of a multidisciplinary team of pharmacy and nursing personnel to coordinate resuscitation and medication administration. The CaRTS group was compared to historical controls. The primary outcome of the study was the proportion of patients with appropriate antibiotic administration within 1 hour of recognition of sepsis. Secondary outcomes included achievement of mean arterial pressure (MAP) ≥65 mm Hg and central venous pressure (CVP) of 8 to 12 mm Hg within 6 hours.Result: The CaRTS intervention was used for 49 patients and 59 historical controls were included for analysis. Patients with the CaRTS intervention had a greater than 20 times higher odds of antibiotic administration within 1 hour compared with controls (odds ratio [OR] 22.4, 95% confidence interval [CI] 7.5-69) and were more likely to have a CVP ≥8 mm Hg at 6 hours (OR 2.4, 95% CI 1.0-5.6) compared with controls. CaRTS patients achieved statistically nonsignificant increases in MAP ≥65 mm Hg (OR 2.2, 95% CI 0.7-7.7).Conclusion: Utilization of a multidisciplinary sepsis bundle that included a pharmacist responder improved the proportion of patients receiving appropriate antibiotics within 1 hour of recognition of sepsis compared to historical controls.